Wood pole structures for electrical transmission lines : recommended practice for design and use - McGuire, James M., 1963-; Lynch, Otto J.; Schneider, Vicki (ASCE Book Series, 2019)
Wood Pole Structures for Electrical Transmission Lines: Recommended Practice for Design and Use, MOP 141, provides comprehensive knowledge of the principles and methods for the design and use of wood poles for overhead utility line structures. The use of wood pole structures, properly designed utilizing consistent structural engineering principles, may provide a simple, cost effective, and more resilient option than some of the other pole materials commonly used.